Kajian Vegetasi Kawasan Pasca Tambang Marmer di Kabupaten Timor Tengah Utara (SAINTEKBU, 2018)
Marble is one of the industrial materials of high economic value and very beneficial to people's lives. Therefore, many explorations are done by mining companies. Exploitation of natural resources on a large scale without regard to the carrying capacity of the environment, can lead to drastic decline in the quality of the ecosystem. This is what happened in the post-mine forest area of ​​Oenbit Village, North Central Timor District. This study aims to identify and calculate the abundance of plants and environmental factors that affect the plants in the post-marble area of ​​Oenbit village. The method used is quadratic / plot method. The results showed that plant species with significant values ​​above 80.00% were Anacardium occidentale L. (125.69%), Tamarindus indica L. (122.17%), Tectona grandis L.f (87.32%), and Schleichera oleosa (Lour .) Oken (82.67%). Abiotic environmental factors measured at the study sites are soil pH, soil moisture, air temperature, air humidity and light intensity. The results of these measurements showed no significant difference.